Seasonal patterns in B‐vitamins and cobalamin co‐limitation in the Northwest Atlantic - Catherine Bannon; Patrick L. White; Elden Rowland; Kiran J. More; Anna Gleason; Megan Roberts; Emmanuel Devred; Lindsay Beazley; Julie LaRoche; Erin M. Bertrand (Limnology and Oceanography, 2025)
B‐vitamins are important co‐enzymes that have long been hypothesized to play key roles in marine ecosystems. However, environmental measurements remain scarce, which limits our understanding of their potential impact. Here, we present mass spectrometry‐based measurements of B‐vitamins (B 1 , B 2 , B 3 , B 5 , B 6 , B 12 ) and related vitamers along a transect in the Northwest Atlantic Ocean, in both particulate phase and dissolved in seawater, seasonally over 5 yr. We then couple these data with targeted investigations of the impact of B 12 (cobalamin) on phytoplankton growth. We show that these metabolites are present at femto‐ to pico‐molar concentrations and demonstrate that season explains most variance in particulate phase B‐vitamins but not dissolved, offering further evidence that metabolite inventories in these two phases are often decoupled. We find positive correlations between particulate organic carbon with particulate B 1 and B 3 , and between chlorophyll a and particulate B 2 and 5,6‐dimethylbenzimidazole in fall but not spring, indicating unique seasonal drivers of vitamin inventories. Of all measured vitamins, only cobalamin was enriched in the particulate over dissolved phase, predominantly in spring. We documented nitrogen and cobalamin co‐limitation of phytoplankton growth during spring bloom decline, when dissolved cobalamin is seemingly drawn down, but not during fall, when dissolved cobalamin concentrations remain elevated. These seasonal differences may be underpinned by the increased importance of cobalamin remodeling and recycling during the fall. This study provides insights into the absolute concentrations, stoichiometry, and variability of B‐vitamins in the ocean and offers evidence that cobalamin exerts seasonally varying controls on Northwest Atlantic marine ecosystems.

A novel GSM and fluorescence coupled full-spectral chlorophyll a algorithm for waters with high CDM content - Juan Li; Atsushi Matsuoka; Emmanuel Devred; Stanford B. Hooker; Xiaoping Pang; Marcel Babin (Remote Sensing of Environment, 2025)

Production and utilization of pseudocobalamin in marine Synechococcus cultures and communities - Catherine C. Bannon; Maria A. Soto; Elden Rowland; Nan Chen; Anna Gleason; Emmanuel Devred; Julie LaRoche; Erin M. Bertrand (Environmental Microbiology, 2024)
Cobalamin influences marine microbial communities because an exogenous source is required by most eukaryotic phytoplankton, and demand can exceed supply. Pseudocobalamin is a cobalamin analogue produced and used by most cyanobacteria but is not directly available to eukaryotic phytoplankton. Some microbes can remodel pseudocobalamin into cobalamin, but a scarcity of pseudocobalamin measurements impedes our ability to evaluate its importance for marine cobalamin production. Here, we perform simultaneous measurements of pseudocobalamin and methionine synthase (MetH), the key protein that uses it as a co‐factor, in Synechococcus cultures and communities. In Synechococcus sp. WH8102, pseudocobalamin quota decreases in low temperature (17°C) and low nitrogen to phosphorus ratio, while MetH did not. Pseudocobalamin and MetH quotas were influenced by culture methods and growth phase. Despite the variability present in cultures, we found a comparably consistent quota of 300 ± 100 pseudocobalamin molecules per cyanobacterial cell in the Northwest Atlantic Ocean, suggesting that cyanobacterial cell counts may be sufficient to estimate pseudocobalamin inventories in this region. This work offers insights into cellular pseudocobalamin metabolism, environmental and physiological conditions that may influence it, and provides environmental measurements to further our understanding of when and how pseudocobalamin can influence marine microbial communities.

Improving Satellite Chlorophyll-a Retrieval in the Turbid Waters of the Bay of Fundy, Canada - Kristen L. Wilson; Andrea Hilborn; Stephanie Clay; Emmanuel Devred (Estuaries and Coasts, 2024)
The Bay of Fundy is a highly productive ecosystem within the Northwest Atlantic where extreme tides and strong currents result in a large gradient of sediment concentrations across and along the bay. We processed daily satellite data from the MODerate resolution Imaging Spectroradiometer (MODIS) on the Aqua satellite from 2003 to 2021 at 300-m resolution to understand and quantify spatial and temporal trends in chlorophyll-a concentration (chl-a, a measure of phytoplankton biomass), and suspended particulate matter concentration (SPM) in the Bay of Fundy surface waters. To account for high sediment loading (up to 100’s g m −3 ) and moderate chl-a (median in situ chl-a of 1.5 mg m −3 from 2003 to 2021), coefficients of the OC3M chl-a algorithm were regionally tuned using in situ chl-a data, and satellite-derived SPM was incorporated within the chl-a retrieval algorithm to account for possible bias. The updated new algorithm was denoted as OC X-SPMCor . Chl-a computed using OC X-SPMCor showed better performance against in situ chl-a than the generic OC3M with a coefficient of determination that increased from 0.01 to 0.28 and a root mean square logarithmic error that decreased by 35%. Unlike previous remote sensing studies, OC X-SPMCor correctly predicted the particular chl-a seasonality in the Bay of Fundy, which does not follow the typical occurrence of spring/fall blooms as observed in the adjacent Gulf of Maine and Scotian Shelf. For the first time, satellite-predicted chl-a aligned with the phenology of in situ chl-a, where chl-a continually increased from April to June and remained high all summer, with a small secondary summer peak before decreasing in the fall. SPM seasonality followed an opposite trend where SPM reached a maximum in winter and a minimum in summer. A small number of matchups and high temporal variability on the hourly time scale precluded a robust assessment of the satellite-derived SPM. However, comparisons between time series of remotely sensed and in situ SPM demonstrated the ability of the satellite-derived SPM to capture temporal variations, though the absolute values may be slightly underestimated. Accurate maps of phytoplankton biomass and sediment concentrations are essential variables required for effective management and conservation of marine ecosystems in the Bay of Fundy.

Seasonal and decadal variations in absorption properties of phytoplankton and non-algal particulate matter in three oceanic regimes of the Northwest Atlantic - Emmanuel Devred; Tim Perry; Philippe Massicotte (Frontiers in Marine Science, 2022)
Seasonal and inter-annual absorption properties of phytoplankton and non-algal particulate matter were studied in relation to phytoplankton biomass, as indexed by chlorophyll-a concentration, and presence of diatoms, as indexed by fucoxanthin concentration, using a 20-year time series of in situ data collected in the Northwest Atlantic. We found significant differences in the spatiotemporal variations of the bio-optical properties for three oceanic regimes: mesotrophic (Scotian Shelf), oligotrophic (Northwest Atlantic Basin, NAB), and subartic (Labrador Sea). The Scotian Shelf and NAB exhibited similar phenology with the spring and autumn blooms associated with low phytoplankton specific absorption, while only relatively high fucoxanthin concentration occurred in spring. The NAB showed a smaller seasonal variation than the Scotian Shelf in agreement with its oceanic conditions. The Labrador Sea showed a single phytoplankton bloom in spring followed by a continuous decrease in biomass the rest of the year. The relationship between phytoplankton absorption coefficient at 443 nm and chlorophyll-a concentration was consistent with other studies with coefficients that were region-dependent. Absorption by non-algal particulate matter remained between 5% and 60% of phytoplankton absorption with a mean of 15%. The slope of the non-algal particulate absorption varied with seasons and regions and appeared to depend on the trophic status with high values (i.e., up to 0.04) occurring during bloom conditions. We also introduced a new index, the phytoplankton apparent absorption wavelength ( PAAW ), a wavelength-weighted sum of absorption expressed in nanometers that provides information on the phytoplankton biomass and assemblage in a simple manner. Time series analysis of the PAAW revealed a decrease of this property in spring on the Scotian Shelf, NAB, and Labrador Sea and an increase in autumn on the Scotian Shelf and NAB, suggesting a shift in these ecosystems.

Delineation of Eastern Beaufort Sea Sub-regions Using Self-Organizing Maps Applied to 17 Years of MODIS-Aqua Data - Andrea Hilborn; Emmanuel Devred (Frontiers in Marine Science, 2022)
Satellite observations are an integral component of long-term Arctic Ocean monitoring and help identifying changes resulting from climate warming. A Self-Organizing Maps (SOM) approach was applied to four-day composite satellite images of the Eastern Beaufort Sea (EBS) acquired by the MODerate resolution Imaging Spectroradiometer over the period 2003–2019. Using sea-surface temperature (SST), suspended particulate matter concentration (SPM) and chlorophyll-a concentration (Chl-a) as input the EBS was partitioned into six biogeochemical regions. The SOM approach revealed region-specific mean conditions and seasonal cycles for all properties, particularly for SPM and Chl-a. Three of the six regions, located on the continental shelf, had the highest SST, SPM and Chl-a with earlier maxima compared to the remaining three regions which comprised the shelf edge, Canada Basin and Amundsen Gulf. While mean and maximum SST did not exhibit significant trends over the 17 years of observations, the annual maximum SST in Amundsen Gulf was reached significantly earlier in recent years compared to the start of the time series. With the exception of Amundsen Gulf, sea-ice concentration (SIC) derived from microwave satellites declined throughout the study area; monthly trends showed dramatic SIC declines in regions on the shelf during May and June, and in Canada Basin during August. Correlation analysis of properties within and between regions showed that SST and SIC were driven by large scale processes while SPM and Chl-a showed regional features. SST and Chl-a in the regions nearest the Mackenzie River showed a strong relationship during seasonal warming. The SOM approach, applied to 17 years of satellite data, revealed spatially distinct marine units with unique characteristics, emphasizing the need for regional considerations when assessing the impact of climate warming in the Arctic Ocean.

MDPI Oceans: A New Publication Channel for Open Access Science Focused on the Ocean - Antonio Bode; Fátima Abrantes; Agostinho Antunes; Alvise Benetazzo; Chen-Tung Arthur Chen; Emmanuel Devred; Martin Gade; Eulàlia Gràcia; Jochen Horstmann; Diego Macías; Joseph M. Maina; Pere Masqué; et al. (Oceans, 2019)
The ocean is the most important subsystem of the Earth’s climate system and functions as its heart, regulating the energy distribution of the planet [...]

Obtaining Phytoplankton Diversity from Ocean Color: A Scientific Roadmap for Future Development - Astrid Bracher; Heather A. Bouman; Robert J. W. Brewin; Annick Bricaud; Vanda Brotas; Aurea M. Ciotti; Lesley Clementson; Emmanuel Devred; Annalisa Di Cicco; Stephanie Dutkiewicz; Nick J. Hardman-Mountford; Anna E. Hickman; et al. (Frontiers in Marine Science, 2017)

A Consumer's Guide to Satellite Remote Sensing of Multiple Phytoplankton Groups in the Global Ocean - Colleen B. Mouw; Nick J. Hardman-Mountford; Séverine Alvain; Astrid Bracher; Robert J. W. Brewin; Annick Bricaud; Aurea M. Ciotti; Emmanuel Devred; Amane Fujiwara; Takafumi Hirata; Toru Hirawake; Tihomir S. Kostadinov; et al. (Frontiers in Marine Science, 2017)

Diagnostic Properties of Phytoplankton Time Series from Remote Sensing - Trevor Platt; Shubha Sathyendranath; George N. White; César Fuentes-Yaco; Li Zhai; Emmanuel Devred; Charles Tang (Estuaries and Coasts, 2010)

Radiative transfer code: Application to the calculation of PAR - Devred Emmanuel; Dubuisson Phillipe; Chami Malik (Journal of Earth System Science, 2000)